2019
DOI: 10.23880/ijoac-16000166
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Soft Shell Mangrove Crab, Scylla Spp. Production in the Southwest Region of Bangladesh

Abstract: The experiment was conducted for a rearing for a period of 150 days from mid-September to mid-February 2017 in three earthen ponds with an installing of 9880 cages per hectare with an average depth of 1.0 meter. The experiment was designed at the ponds of Kaligonj Chingri Farm as a treatment T1, Allarchar chingri farm as a treatment T2 and Shamnagar private crab farm as a treatment T3. Before stocking crabs were categorized at five size groups. At stocking, all crabs were with an initial mean carapace width an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…In this study, the range of alkalinity in the culture pond of Scylla serrata was found in between 50 and 133 mg/l with a mean of 104.67±6.83mg/l. Chakraborty (2019) recorded water alkalinity ranging from 127.48±7.14 to 136.08±8.44mg/l in the three crab culture earthen ponds in the South west region of Bangladesh which is a little bit higher than the present study. However, Hossain (2007) recorded the soil alkalinity values of 41.10 ppm and 69.70 ppm in the two experimental stations of the mangrove swamp forest of Chakaria, Sundarban, Bangladesh, while Zafar and Hasan (2005) recorded the values of soil alkalinity from 49.0 to 52.5 ppm at Poshur River mangrove fringe, Sundarban.…”
Section: Water Qualitycontrasting
confidence: 81%
See 1 more Smart Citation
“…In this study, the range of alkalinity in the culture pond of Scylla serrata was found in between 50 and 133 mg/l with a mean of 104.67±6.83mg/l. Chakraborty (2019) recorded water alkalinity ranging from 127.48±7.14 to 136.08±8.44mg/l in the three crab culture earthen ponds in the South west region of Bangladesh which is a little bit higher than the present study. However, Hossain (2007) recorded the soil alkalinity values of 41.10 ppm and 69.70 ppm in the two experimental stations of the mangrove swamp forest of Chakaria, Sundarban, Bangladesh, while Zafar and Hasan (2005) recorded the values of soil alkalinity from 49.0 to 52.5 ppm at Poshur River mangrove fringe, Sundarban.…”
Section: Water Qualitycontrasting
confidence: 81%
“…Crab farmers collect the mud crab during this time as soft shell crab (Oesterling and Moore 1995). Soft shell crabs are in high demand in international markets due to their easy edibility in comparison to hard shell crabs and their high nutritional value (Chakraborty 2019). The commonly cultivated soft shell crabs are blue swimmer crab (Portunus pelagicus) and mud crab (Scylla serrata) (Niswar et al 2018), while Scylla sp.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, when there is a shelter nearby, the frequency of molting increases [6]. According to research, the time of molting was higher at night, particularly during night high tides [4], [15]. Because the molting itself causes mud crabs vulnerable to cannibalism or predation [8].…”
Section: Incidence Of Molting Between Tidal Episodes and Water Currentmentioning
confidence: 99%
“…Furthermore, results supported the statement of Hosamani et al (2016) that molting is affected by temperature and photoperiod. A related study by Chakraborty (2019) also found that the time of molting (Scylla spp.) was during nighttime at 60-70% more than day time.…”
Section: Diurnal Cycle Of Moltingmentioning
confidence: 84%